Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Dengan Metode Weighted Product - Fitria Sari; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
School is one of the facilities that used for studying. All of teachers in that school do an assessment for students, this assessment has the function for measuring the extent of student achievement f or one semester in teaching and learning process at SMP Smart Indonesia Pekanbaru. The aspects that assessed are Academic and Non Academic Aspects. Academic Aspects which is include of Main Subjects and Muatan Lokal Subjects, then Non-Academic aspects which is includes of students’ Creativity, Students’Attitudes, and Students’ Absent. The selection of students’ achievement at SMP Smart Indonesia is still done manually and relatively take a long time. So far the selection of students’ achievement has only been determined by based on the Academic Assessment Aspects. So that in selecting of students’ acievement can be done quickly, precisely, fairly and able to combine about Academic and Non-Academic Apects, the researchers built a Decision Support System for Student Achievement Selection with the Weighted Product Method. Weighted Product Method is a decision making method that uses multiplication to link attribute ratings, where the rating of each attribute must be raised first with the weight of the attribute in question. By using this system, it can be easier for the school to select students’ achievement. To create a system that aims to select high-achieving students, the researchers took a data collection process that included do an observation with the SMP Smart Indonesia directly, interviews with the Principal, and gave a questionnaire to the teachers in the SMP Smart Indonesia. The calculation results obtained from the system built, which compared with the manual calculation results Weighted Product Method has a value of 100% conformity calculation calculation. Testing the use of this system was also carried out by the school with the results of the assessment percentage of 93.74%, obtained from the accumulation of observations, interviews and questionnaires given to six respondents. These respondents consisted of all teachers at SMP Smart Indonesia. So, it can be concluded that the Achievement Student Support Decision Support System with the Weighted Product Method is feasible to be used in the SMP Smart Indonesia Pekanbaru environment Keywords : Decision Support System, Student Achievement, Weighted Product, SMP Smart Indonesia..